Auditory cues assist patients with Parkinson’s disease (on and off L-dopa) during obstacle crossing - Rinaldi, Natalia Madalena (2019)
People with Parkinson’s disease (PD) have an impaired locomotor pattern. As a result, the capacity of walking independently and the interaction with the environment can be impairment. Uneven environments can challenge even more the motor control of these patients to perform the locomotor tasks successfully. Besides of the levodopa therapy, the auditory cues have also been utilized to improve the gait parameters. However, the effects of auditory cues in gait during obstacle avoidance and the association with the levodopa effects are not known. The aim of this study was to investigate the effects of AC during obstacle crossing in people with PD (on and off L-dopa) and in healthy control participants.A total of 30 individuals participated in the study, including 15 PD patients who were tested both on and off L-dopa and 15 healthy adult controls. The task consisted of stepping over an obstacle located in the middle of the path under two conditions, i.e., cued and non-cued. We used  kinematic, kinetic and electromyographic analyses to evaluate individuals' locomotor patterns. Groups differed signifi cantly from each other for all analyses and PD patients differed signifi cantly from all other groups when off L-dopa. ACs improved the motor control mechanisms used for obstacle crossing in people with PD. These results support the notion that external AC therapy may be used as a complement to drug therapy tohelp improve locomotion in PD patients, even on complex tasks such as obstacle crossing.